Bibliometric Analysis of Problem-Based Learning Model with STEM Approach: Critical Thinking Skills of Elementary School Students - Azhari, Rafa Adilla; Hidayah, Nurul; Diani, Rahma; Kalifah, Diah Rizki Nur (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Elementary schools must creatively develop critical thinking abilities to equip students with 21st-century competencies. Analyzing previous research on integrating learning models for this purpose is necessary. This study will bibliometrically analyze the research on integrating the Problem-Based Learning (PBL) model with the Science, Technology, Engineering, and Mathematics (STEM) approach to improve elementary school critical thinking. VOSviewer software was used to conduct a systematic literature review and bibliometric analysis of 52 Scopus-indexed articles from 2020–2024. Publish or Perish (PoP), linked to Scopus, collected publication data using